Positive electrode material and preparation method thereof, and preparation method of CuCo double-monatomic material
By using CuCo double single atomic material in the positive electrode material of lithium sulfur batteries, the performance attenuation problem caused by the polysulfide shuttle effect is solved, and the specific capacity, rate performance and cycle performance of lithium sulfur batteries are improved.
Patent Information
- Application Number
- CN202311222914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
Lithium sulfur batteries have performance decays due to the shuttle effect of polysulfides, including degradation of specific capacity, rate performance and cycle performance.
CuCo di-monoatomic material is used as the key component of the cathode material, and CuCo di-monoatomic material is prepared by a two-step method, so that copper and cobalt atoms exist in the MOF organic framework derivatized carbon respectively, enhancing the interaction between active sites and polysulfides.
It significantly alleviates the shuttle effect of polysulfides and improves the specific capacity, rate performance and cycling performance of lithium-sulfur batteries.
Smart Images

Figure CN119673981A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and specifically provides a positive electrode material and a preparation method thereof, as well as a preparation method of a CuCo double single atom material. Background Art
[0002] As electric vehicles, portable electronic products and other devices continue to increase the energy density of energy storage batteries, the energy density of lithium-ion batteries cannot meet the demand. Therefore, new energy storage batteries with higher energy density and longer cycle life have attracted much attention. Thanks to the high specific capacity of both positive and negative active materials, lithium-sulfur batteries have a very high theoretical energy density (2600Wh / kg) and are considered to be the development direction of the next generation of energy storage and power batteries.
[0003] However, the practical application of lithium-sulfur batteries still faces some challenges, such as the low electronic conductivity of elemental sulfur and discharge end products (e.g., Li2S2, Li2S, etc.), the long-chain polysulfides formed as intermediate products during the charge and discharge process (e.g., Li2S x , x ≥ 4, etc.) are easily soluble in organic electrolytes, causing the loss of positive electrode active materials, and then migrate to the negative electrode of the battery through the porous diaphragm, and react with the negative electrode. After that, the polysulfides will shuttle back and forth between the positive and negative electrodes. This process is called the "shuttle effect". The shuttle effect is considered to be one of the most critical factors leading to the performance degradation of lithium-sulfur batteries. In addition, the multi-electron reaction kinetics of the sulfur positive electrode are slow, which will lead to the accumulation of soluble polysulfides, aggravate the shuttle effect of polysulfides, and further deteriorate the rate performance, discharge specific capacity and cycle performance of lithium-sulfur batteries. The redox of sulfur is a complex reaction with multiple electrons and steps. It is difficult for a single catalytic site to achieve catalytic reactions involving multiple intermediates, and it is difficult to achieve simultaneous acceleration of multi-step bidirectional reaction kinetics.
[0004] Accordingly, the art needs a new technical solution to solve the above problems. Summary of the invention
[0005] The present invention aims to solve the above technical problem, that is, to solve the problem that the performance of existing lithium-sulfur batteries is attenuated due to the shuttle effect of polysulfides.
[0006] In a first aspect, the present invention provides a positive electrode material, which includes sulfur and a CuCo di-monoatom material, wherein the sulfur is loaded on the CuCo di-monoatom material, and the CuCo di-monoatom material is prepared by the following steps: Step 1, preparation of Cu single-atom material: mixing an inorganic salt with the copper metal organic framework material, and obtaining the Cu single-atom material after a first heat treatment; Step 2, preparation of CuCo di-monoatom material: mixing the Cu single-atom material, a cobalt source and a solvent to obtain a second mixed solution, drying the second mixed solution and performing a second heat treatment to obtain the CuCo di-monoatom material.
[0007] Furthermore, the copper metal organic framework material is formed by the coordination of Cu atoms and organic ligands, and the organic ligands include 1,4-phthalic acid, trimesic acid or 2,5-dihydroxyterephthalic acid.
[0008] Furthermore, the preparation method of the CuCo di-monoatom material satisfies at least one of the following conditions: (1) the first heat treatment is carried out under an inert atmosphere; (2) the temperature of the first heat treatment is 700°C to 800°C; (3) the treatment time of the first heat treatment is 2h to 5h; (4) the second heat treatment is carried out under an inert atmosphere; (5) the temperature of the second heat treatment is 700°C to 900°C; (6) the treatment time of the second heat treatment is 2h to 5h.
[0009] Furthermore, the preparation method of the CuCo diatomic material satisfies at least one of the following conditions: (1) the cobalt source is vitamin B12; (2) the solvent is ethanol; (3) the inorganic salt includes KCl and NaCl.
[0010] Furthermore, the preparation method further comprises: in the step 1, after the first heat treatment, pickling is performed using an acidic solution to obtain the Cu single atom material; wherein the pH value of the acidic solution ranges from 1 to 7.
[0011] Furthermore, the copper metal organic framework material is prepared by the following method: an organic ligand is mixed with a solution containing copper ions, and the mixture is filtered after reaction to obtain the copper metal organic framework material.
[0012] The positive electrode material of the present invention is added with a CuCo double single-atom material, which is prepared by first preparing a Cu single-atom material and then reacting the Cu single-atom material with a cobalt source. That is, in the preparation process of the CuCo double single-atom material, the copper ions and cobalt ions in the copper source and the cobalt source are respectively reduced in two steps and attached to the derived carbon material after high-temperature carbonization of the MOF organic framework, which can avoid the aggregation of copper atoms and cobalt atoms to form copper metal particles, cobalt metal particles, or copper-cobalt bimetallic particles during the reduction process, so that copper and cobalt exist in atomic form respectively. The positive electrode material having the CuCo double single-atom material also has a large number of copper atoms and cobalt atoms, and each metal atom can serve as an active site. In this way, the positive electrode material also has a large number of active sites. Under the synergistic effect of the copper atom and cobalt atom double-atom sites, the interaction between each active site and the polysulfide can be enhanced, and the activity of each site can be improved, thereby accelerating the conversion reaction kinetics in the polysulfide redox process, promoting the uniform deposition of lithium sulfide, and greatly alleviating the shuttling effect of polysulfides, thereby improving the specific capacity, rate performance and cycle performance of the lithium-sulfur battery having the positive electrode.
[0013] In a second aspect, the present invention provides a method for preparing a CuCo double single-atom material for a lithium-sulfur battery, comprising the following steps:
[0014] Step 1: Preparation of Cu single atom material:
[0015] The inorganic salt is mixed with the copper metal organic framework material, and a Cu single atom material is obtained after a first heating treatment;
[0016] Step 2: Preparation of CuCo double single atom materials:
[0017] The Cu single-atom material, a cobalt source and a solvent are mixed to obtain a second mixed solution, and the second mixed solution is dried and then subjected to a second heat treatment to obtain the CuCo double single-atom material.
[0018] In the case of adopting the above technical solution, the copper in the copper source is first reduced and attached to the MOF organic framework derived carbon to prepare a Cu single atom material, and then the cobalt in the cobalt source is reduced and attached to the Cu single atom material to prepare a CuCo double single atom material. In this preparation process, the copper atoms and cobalt atoms obtained after reduction can be prevented from aggregating to form copper metal particles, cobalt metal particles, or copper-cobalt double metal particles, so that copper and cobalt can each exist in atomic form and dispersed in the MOF organic framework derived carbon. Each metal atom can serve as an active site, and compared with the existence in the form of metal particles, the active sites in the CuCo double single atom material are increased. Each active site is dispersed in the MOF organic framework and can be more fully in contact with the outside world, thereby effectively improving the utilization rate of metal atoms in the CuCo double single atom material.
[0019] In a third aspect, the present invention provides a method for preparing the aforementioned positive electrode material, comprising the following steps: mixing sulfur with CuCo dimonoatom material, and obtaining the positive electrode material through a third heat treatment.
[0020] Furthermore, the sulfur is elemental sulfur, and the elemental sulfur is sublimated sulfur; and / or, the ratio of the sulfur to the CuCo diatomic material is 9:1 to 6:4.
[0021] Furthermore, the third heat treatment is performed under an inert atmosphere, the third temperature of the third heat treatment is 130° C. to 160° C., and the third treatment time is 10 h to 13 h.
[0022] The present invention mixes the CuCo double single-atom material prepared by the two-step method with sulfur at a relatively low temperature, so that the sulfur content in the positive electrode can be accurately controlled, and thus a lithium-sulfur battery that meets the expectations can be prepared more accurately. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings, in which:
[0024] Figure 1 A discharge specific capacity test curve diagram of an electrochemical test in an embodiment of the present invention;
[0025] Figure 2 It is a curve chart of lithium sulfide nucleation experiment in one embodiment of the present invention. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0027] The present invention provides a material, which includes a CuCo double single-atom material, and the CuCo double single-atom material is prepared by the following steps:
[0028] Step 1: Preparation of Cu single atom material:
[0029] The organic ligand is mixed with a solution containing Cu ions, a complex reaction is carried out, and the solution is filtered to obtain a copper metal organic framework material (hereinafter referred to as Cu-MOF).
[0030] The inorganic salt and Cu-MOF are mixed uniformly in a mass ratio of 40:1, and the Cu single atom material is obtained after a first heating treatment in an atmosphere tube furnace;
[0031] Step 2: Preparation of CuCo double single atom materials:
[0032] The Cu single atom material and the cobalt source in a mass ratio of 1:1 are dispersed in a solvent, stirred to make the Cu single atom material and the cobalt source evenly mixed to form a second mixed liquid, and after the second mixed liquid is dried, a second heat treatment is performed in an atmosphere tube furnace to obtain a CuCo double single atom material.
[0033] Through the above-mentioned preparation method, a CuCo double single-atom material is added to the positive electrode material, and the CuCo double single-atom material is prepared by first preparing a Cu single-atom material, and then the Cu single-atom material is reacted with a cobalt source. That is to say, in the process of preparing the CuCo double single-atom material, the copper ions and cobalt ions in the copper source and the cobalt source are respectively reduced and attached to the derived carbon material after the MOF organic framework is carbonized at high temperature by a two-step method, which can avoid the aggregation of copper atoms and cobalt atoms to form copper metal particles, cobalt metal particles, or copper-cobalt bimetallic particles during the reduction process, so that copper and cobalt exist in atomic form and are dispersed in the MOF organic framework derived carbon. The CuCo double single-atom material also has a lot of copper atoms and cobalt atoms, and each metal atom can be used as an active site, so that the positive electrode material also has more active sites, which effectively increases the active sites in the CuCo double single-atom material. Moreover, under the synergistic effect of the diatomic sites of copper atoms and cobalt atoms, the interaction between each active site and polysulfide can be enhanced, and the activity of each site can be improved, thereby accelerating the conversion reaction kinetics in the polysulfide redox process, promoting the uniform deposition of lithium sulfide, and greatly alleviating the shuttle effect of polysulfide, thereby improving the specific capacity, rate performance and cycle performance of lithium-sulfur batteries with this positive electrode.
[0034] In practical applications, organic ligands and copper atoms can be complexed to form Cu-MOFs with different structures, such as Cu-HKUST-1 or Cu-MOF-74, etc. The colors of Cu-MOFs with different structures will be different. The change in the color of Cu-MOF should not be understood as limiting the scope of protection of the present invention.
[0035] In practical applications, the aqueous solution containing copper ions can be a copper sulfate solution, a copper nitrate solution, a copper chloride solution, etc. Such adjustment and change of the specific type of the solution containing copper ions does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0036] In practical applications, the organic ligand may be 1,4-phthalic acid, trimesic acid or 2,5-dihydroxyterephthalic acid. Such adjustment and change of the specific type of organic ligand does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0037] In practical applications, Cu-MOF can be prepared by solvothermal method, hydrothermal method or solvothermal method in oil bath. Obviously, those skilled in the art can also prepare Cu-MOF by electrochemical synthesis methods such as anodic synthesis method, cathodic synthesis method, indirect bipolar electrodeposition method, electric displacement method and electrophoretic deposition method. Taking anodic synthesis method as an example, copper plate is used as anode and cathode, methanol solution containing 1,3,5-benzenetricarboxylic acid is used as electrolyte, and electricity is applied for electrolytic reaction to prepare Cu-MOF. Such adjustment and change of the method for preparing Cu-MOF does not deviate from the principle and scope of the present invention, and should be included in the protection scope of the present invention.
[0038] Further, the first heat treatment is performed in an inert atmosphere, such as an argon atmosphere, a helium atmosphere, etc., and the temperature of the first heat treatment is 700° C. to 800° C., for example, the temperature may be 700° C., 730° C., 750° C., 780° C., 800° C., etc. The time of the first heat treatment is 2 h to 5 h, for example, the time may be 2 h, 3 h, 4 h, 5 h, etc.
[0039] Further, the second heat treatment is performed under an inert atmosphere, and the temperature of the second heat treatment is 700° C. to 900° C., for example, the temperature may be 700° C., 750° C., 780° C., 800° C., 850° C., 900° C., etc. The time of the second heat treatment is 2 h to 5 h, for example, the time may be 2 h, 3 h, 4 h, 5 h, etc.
[0040] It should be noted that, without departing from the basic principles of the present application, the above-mentioned adjustments and changes to the temperature and time do not deviate from the principles and scope of the present invention, and should be included in the protection scope of the present invention.
[0041] Preferably, the temperature of the second heat treatment is 700° C., at which the performance of the prepared CuCo double single-atom material is optimal.
[0042] Furthermore, the inorganic salt in step 2 is a mixture of KCl and NaCl. Under the conditions of an atmosphere tube furnace and high temperature, KCl and NaCl form a molten salt that can dissolve and disperse Cu-MOF. The molten salt formed by KCl and NaCl is relatively stable at high temperatures and will not produce side reactions.
[0043] Specifically, the inorganic salt is formed by mixing KCl and NaCl in a mass ratio of 1:1. The melting point of the inorganic salt at this ratio is the smallest, and the inorganic salt can be molten at a relatively low temperature.
[0044] In practical applications, the mass ratio of KCl and NaCl in the inorganic salt can also be 2:1, 1:2, 1:3, 3:1, etc. Such adjustment and change of the mass ratio of KCl and NaCl in the inorganic salt does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0045] Specifically, the mass ratio of the inorganic salt to the Cu-MOF is 1:(30-50), for example, the mass ratio of the inorganic salt to the Cu-MOF is 1:30, 1:40, 1:50, etc. Within this ratio range, the Cu-MOF can be better dispersed in the molten inorganic salt, and thus the Cu-MOF can be better converted into the Cu single-atom material, thereby improving the conversion efficiency of the Cu-MOF to the Cu single-atom material.
[0046] In practical applications, those skilled in the art can adjust the types of inorganic salts according to actual conditions, for example, lithium chloride, potassium nitrate, etc. can be used, and the mass ratio of the inorganic salts can also be adjusted according to actual conditions. Such adjustments and changes to the types of inorganic salts used and the proportions of inorganic salts used do not deviate from the principles and scope of the present invention and should be included in the protection scope of the present invention.
[0047] In practical applications, those skilled in the art may select inorganic salts and Cu-MOFs with other mass ratios. Such adjustments and changes to the mass ratio of inorganic salts and Cu-MOF do not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0048] Furthermore, the cobalt source in step three is vitamin B12, which has a low cost and can effectively reduce the cost of preparing CuCo diatomic materials, thereby reducing the cost of preparing the positive electrode of the lithium-sulfur battery.
[0049] In practical applications, those skilled in the art may also use other types of cobalt sources, such as cobalt nitrate, etc. Such adjustments and changes to the cobalt source do not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0050] Furthermore, the solvent in step 2 is ethanol, which can disperse the Cu single atom material and the cobalt source and does not react with the Cu single atom material and the cobalt source. In addition, ethanol is cheap and easy to obtain. When the Cu single atom material and the cobalt source are evenly mixed and dried, there will be no ethanol residue, thereby not affecting the reaction of the Cu single atom material and the cobalt source in the atmosphere tube furnace.
[0051] In practical applications, the solvent may also be methanol, isopropanol, etc. Such adjustment and change of the solvent does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0052] It should be noted that the solvent in step 1 may also be an ether solvent, a ketone solvent, an alkane solvent, etc. Such adjustment and change of the solvent does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0053] Furthermore, the preparation method further includes: in step 1, after the reaction of the inorganic salt and the Cu-MOF is completed, that is, after the first heat treatment, the obtained reaction product is washed with deionized water, then soaked with an acidic solution, washed with deionized water until neutral, and dried under vacuum to obtain a Cu single-atom material. In this way, by soaking and washing the reaction product with an acidic solution, the residual copper ion compounds in the product can be removed, thereby improving the purity of the Cu single-atom material.
[0054] In practical applications, the acidic solution can be a concentrated hydrochloric acid solution with a pH value in the range of 1 to 7, or a concentrated nitric acid solution, etc. Such adjustment and change of the acidic solution does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention.
[0055] In practical applications, in step one, after the reaction of the inorganic salt and Cu-MOF is completed, the obtained second mixture can be directly cooled without acid washing, so that Cu single-atom material can also be obtained. This adjustment and change of the post-treatment method of the reaction product does not deviate from the principle and scope of the present invention, and should be included in the protection scope of the present invention.
[0056] In a second aspect, the present invention provides a method for preparing a CuCo double single-atom material, comprising the following steps:
[0057] Step 1: Preparation of Cu single atom material:
[0058] The organic ligand is subjected to a complexation reaction with a solution containing copper ions, and the reaction is filtered to obtain Cu-MOF;
[0059] The inorganic salt and the Cu-MOF are mixed, and a Cu single atom material is obtained after a first heating treatment;
[0060] Step 2: Preparation of CuCo double single atom materials:
[0061] The Cu single-atom material, the cobalt source and the solvent are mixed to obtain a second mixed solution, and the second mixed solution is dried and then subjected to a second heat treatment to obtain a CuCo double single-atom material.
[0062] In the case of adopting the above technical solution, the copper in the copper source is first reduced and attached to the organic ligand to prepare a Cu single-atom material, and then the cobalt in the cobalt source is reduced and attached to the Cu single-atom material to prepare a CuCo double single-atom material. In the preparation process, only the copper atom is in a free state in step 2, and only the cobalt atom is in a free state in step 3, so that copper and cobalt can be dispersed more in the MOF organic framework-derived carbon in atomic form, rather than agglomerating to form copper metal particles, cobalt metal particles, or copper-cobalt bimetallic particles. In other words, through such a two-step preparation method, copper and cobalt can each exist in atomic form and be dispersed in the MOF organic framework-derived carbon, and each metal atom can serve as an active site. Compared with the existence in the form of metal particles, the CuCo double single-atom material obtained by the preparation method of the present invention has more active sites, and there is a synergistic effect between the two atomic sites of each copper atom and the cobalt atom, which can improve the activity of each site. Moreover, the active sites are dispersed in the MOF organic framework and can contact the outside world more fully, thereby effectively improving the utilization rate of metal atoms in the CuCo double single atom material.
[0063] In a third aspect, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0064] Sulfur is mixed evenly with the CuCo double single atom material prepared as described above, and a positive electrode material is obtained by a third heating treatment, namely, a CuCo double single atom positive electrode material loaded with elemental sulfur, referred to as a CuCo-S sulfur positive electrode. Then, the CuCo-S sulfur positive electrode prepared as described above is mixed with a binder according to a set ratio, N-methylpyrrolidone is added to the mixture, and a slurry is obtained by mixing, and the slurry is applied to a current collector to obtain a positive electrode.
[0065] Furthermore, the sulfur is elemental sulfur, which is sublimated sulfur. The sublimated sulfur can evenly fill the atmosphere tube furnace and the gaps between the CuCo dimonoatom materials, thereby increasing the reaction contact area between sulfur and the CuCo dimonoatom materials and improving the dispersion effect of elemental sulfur. It should be noted that sulfur has a variety of crystal forms, and sublimated sulfur is a form of sulfur that is obtained by high-temperature sublimation and subsequent recondensation of sulfur.
[0066] In actual operation, those skilled in the art may also use the elemental sulfur in the form of a ground solid powder. Such adjustment and change of the form of the elemental sulfur during the reaction does not deviate from the principle and scope of the present invention and should be included in the protection scope of the present invention. In addition, the sulfur may be a sulfur compound, such as lithium sulfide, in addition to elemental sulfur.
[0067] Furthermore, the mass percentage of elemental sulfur and CuCo double monoatomic material is 9:1 to 6:4, so as to provide sufficient elemental sulfur for the preparation of CuCo-S sulfur positive electrode, which is more conducive to the preparation of the expected positive electrode material. In actual operation, the mass percentage of elemental sulfur and CuCo double monoatomic material can be 9:1, 8:2, 7:3, 6:3, etc. Such adjustment and change of the mass ratio of elemental sulfur and CuCo double monoatomic material does not deviate from the principle and scope of the present invention, and should be included in the protection scope of the present invention.
[0068] Furthermore, the binder is polyvinylidene fluoride (PVDF), and the adhesiveness of the slurry can be increased by polyvinylidene fluoride.
[0069] Specifically, the binders that can be selected include polyacrylic acid (PAA) and its salt binders, polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), etc. Such adjustments and changes to the binders do not deviate from the principles and scope of the present invention and should be included in the protection scope of the present invention.
[0070] Furthermore, the mass ratio of the CuCo-S sulfur positive electrode to the binder PVDF is 9:1.
[0071] In actual operation, those skilled in the art may also adopt a mass ratio of CuCo-S sulfur positive electrode to binder PVDF of 9:2, 8:1, etc. Such adjustment and change of the mass ratio of CuCo-S sulfur positive electrode to binder PVDF does not deviate from the principle and scope of the present invention, and should be included in the protection scope of the present invention.
[0072] Further, the third heat treatment is carried out in an inert atmosphere, and the temperature of the third heat treatment is 130°C to 160°C, and the time is 10h to 13h. For example, the temperature can be 130°C, 140°C, 145°C, 150°C, 155°C, 160°C, etc., and the time can be 10h, 11h, 12h, 13h, etc. In actual operation, those skilled in the art can also flexibly select temperature and time according to specific application scenarios. Such adjustment and change of temperature and time do not deviate from the principle and scope of the present invention, and should be included in the protection scope of the present invention.
[0073] The present invention first prepares a CuCo double single-atom material through two-step high-temperature treatment. The CuCo double single-atom material has good conductivity and is suitable as a sulfur host material. Then, it is mixed with sulfur at a relatively low temperature (such as 155°C, etc.) below the boiling point of sulfur. At this temperature, the sulfur will not volatilize, and there will be no problem of sulfur loss. In this way, the sulfur content in the positive electrode can be accurately controlled, so that a lithium-sulfur battery that meets the expectations can be prepared more accurately. By accurately controlling the sulfur content, it is beneficial to prepare a positive electrode with a high sulfur content and improve the battery performance of the lithium-sulfur battery.
[0074] The following is an example of obtaining Cu-MOF by reacting terephthalic acid and copper sulfate solution, and combined with Examples 1 to 3 and Comparative Examples to specifically illustrate the preparation method of the CuCo double monoatom material of the present invention. It should be noted that all raw materials used in the preparation process are commercially available products.
[0075] Embodiment 1:
[0076] The preparation method of CuCo double single atom material comprises the following steps:
[0077] Step 1: Preparation of Cu-MOF
[0078] 12 mmol of terephthalic acid (H2BDC) and 25 mmol of NaOH were dissolved in 300 mL of deionized water. After stirring at room temperature for 30 min, 60 mL of 0.25 mol / L copper sulfate aqueous solution was slowly added dropwise. After stirring at room temperature for 5 h, the precipitate was filtered and washed with deionized water and dried at 60 °C in vacuum to obtain Cu-MOF.
[0079] Step 2, preparation of Cu single metal atom catalyst:
[0080] KCl and NaCl were mixed in a mass ratio of 1:1 to form an inorganic salt.
[0081] Cu-MOF and inorganic salt were mixed in a mass ratio of 1:40 and ground to mix evenly, placed in an atmosphere tube furnace, treated at 750°C for 3 hours under an argon atmosphere, then washed with deionized water, soaked in concentrated hydrochloric acid for 4 hours, and then washed with deionized water until neutral, and vacuum dried to obtain Cu single atom material.
[0082] Step 3: Preparation of CuCo double single atom materials
[0083] 0.1 g of Cu single atom material and 0.1 g of vitamin B12 were dispersed in 20 ml of ethanol, stirred evenly and dried, then placed in an atmosphere tube furnace and treated at 800°C for 2 h under argon atmosphere, and naturally cooled to room temperature to obtain the CuCo double single atom material.
[0084] Embodiment 2:
[0085] The preparation method of CuCo double single atom material comprises the following steps:
[0086] Step 1: Preparation of Cu-MOF
[0087] 12 mmol of terephthalic acid (H2BDC) and 25 mmol of NaOH were dissolved in 300 mL of deionized water. After stirring at room temperature for 30 min, 60 mL of 0.25 mol / L copper sulfate aqueous solution was slowly added dropwise. After stirring at room temperature for 5 h, the precipitate was filtered and washed with deionized water and dried at 60 °C in vacuum to obtain Cu-MOF.
[0088] Step 2: Preparation of Cu single metal atom catalyst
[0089] KCl and NaCl were mixed in a mass ratio of 1:1 to form an inorganic salt.
[0090] Cu-MOF and inorganic salt were mixed in a mass ratio of 1:40 and ground to mix evenly, placed in an atmosphere tube furnace, treated at 750°C for 3 hours under an argon atmosphere, then washed with deionized water, soaked in concentrated hydrochloric acid for 4 hours, and then washed with deionized water until neutral, and vacuum dried to obtain Cu single atom material.
[0091] Step 3: Preparation of CuCo double single atom materials
[0092] 0.1 g of Cu single atom material and 0.1 g of vitamin B12 were dispersed in 20 mL of ethanol, stirred evenly and dried, then placed in an atmosphere tube furnace and treated at 900 °C for 2 h under argon atmosphere, and naturally cooled to room temperature to obtain the CuCo double single atom material.
[0093] Embodiment three:
[0094] The preparation method of CuCo double single atom material comprises the following steps:
[0095] Step 1: Preparation of Cu-MOF
[0096] 12 mmol of terephthalic acid (H2BDC) and 25 mmol of NaOH were dissolved in 300 mL of deionized water. After stirring at room temperature for 30 min, 60 mL of 0.25 mol / L copper sulfate aqueous solution was slowly added dropwise. After stirring at room temperature for 5 h, the precipitate was filtered and washed with deionized water and dried at 60 °C in vacuum to obtain Cu-MOF.
[0097] Step 2: Preparation of Cu single metal atom catalyst
[0098] KCl and NaCl were mixed in a mass ratio of 1:1 to form an inorganic salt.
[0099] Cu-MOF and inorganic salt were mixed in a mass ratio of 1:40 and ground to mix evenly, placed in an atmosphere tube furnace, treated at 750°C for 3 hours under an argon atmosphere, then washed with deionized water, soaked in concentrated hydrochloric acid for 4 hours, and then washed with deionized water until neutral, and vacuum dried to obtain Cu single atom material.
[0100] Step 3: Preparation of CuCo double single atom materials
[0101] 0.1 g of Cu single atom material and 0.1 g of vitamin B12 were dispersed in 20 mL of ethanol, stirred evenly and dried, then placed in an atmosphere tube furnace and treated at 700 ° C for 2 h under argon atmosphere, and naturally cooled to room temperature to obtain the CuCo double single atom material.
[0102] In the above three embodiments of the preparation method of CuCo di-monoatom materials, experiments have found that when preparing CuCo di-monoatom materials, CuCo di-monoatom materials can be obtained by reacting at 700°C, 800°C, and 900°C in an argon atmosphere. The carbonization rate of the MOF organic framework material is low, and the copper atoms and cobalt atoms can be dispersed in the MOF organic framework-derived carbon in atomic form respectively. The prepared CuCo di-monoatom materials have better performance.
[0103] Comparative Example 1:
[0104] The preparation method of the comparative material Cu single atom material is as follows:
[0105] Step 1: Preparation of Cu-MOF
[0106] 12 mmol of terephthalic acid (H2BDC) and 25 mmol of NaOH were dissolved in 300 mL of deionized water. After stirring at room temperature for 30 min, 60 mL of a 0.25 mol / L aqueous copper sulfate solution was slowly added dropwise. After stirring at room temperature for 5 h, the precipitate was filtered and washed with deionized water and dried at 60 °C in vacuum to obtain Cu-MOF.
[0107] Step 2: Preparation of Cu single atom materials
[0108] KCl and NaCl were mixed in a mass ratio of 1:1 to form an inorganic salt.
[0109] The Cu-MOF prepared in step 1 was mixed with an inorganic salt in a mass ratio of 1:40 and ground to mix evenly, placed in an atmosphere tube furnace, treated at 750°C for 3 hours under an argon atmosphere, then washed with deionized water, soaked in concentrated hydrochloric acid for 4 hours, then washed with deionized water until neutral, and vacuum dried to obtain a Cu single atom material.
[0110] The lithium sulfide nucleation experiment is based on the materials prepared in Examples 1 to 3, including the CuCo double single-atom material, and based on the materials prepared in Comparative Example 1, including the Cu single-atom material, to evaluate its catalytic performance. Specifically, the lithium sulfide nucleation experiment is carried out using the CuCo double single-atom material and the Cu single-atom material prepared in Example 3 and Comparative Example 1 as examples to illustrate.
[0111] Lithium sulfide nucleation experiment 1:
[0112] Sulfur powder and lithium sulfide in a mass ratio of 7:1 were added to tetraethylene glycol dimethyl ether solvent, and 1 mol of lithium bis(trifluoromethylsulfonate)imide (LiTFSI) was added, and stirred at 60°C for 24 hours to prepare Li2S8 positive electrode electrolyte.
[0113] A circular carbon paper with a diameter of 12 mm was used to prepare the current collector.
[0114] The CuCo double single atom material was dispersed in ethanol and then drop-coated on the current collector. The electrode was dried at 60°C overnight, and the coating loading was controlled to be about 0.5 mg / cm 2 To make a modified electrode sheet.
[0115] During assembly, 40 μL of Li2S8 positive electrode electrolyte was added to the modified electrode sheet. After adding the diaphragm, 20 μL of blank electrolyte was added. The blank electrolyte was prepared by replacing the lithium sulfide in the above-mentioned Li2S8 positive electrode electrolyte with lithium nitrate. The negative electrode used a metallic lithium sheet to assemble a lithium-sulfur battery containing CuCo double single-atom material.
[0116] Lithium sulfide nucleation experiment 2:
[0117] Sulfur powder and lithium sulfide in a mass ratio of 7:1 were added to tetraethylene glycol dimethyl ether solvent, and 1 mol of lithium bis(trifluoromethylsulfonate)imide (LiTFSI) was added, and stirred at 60°C for 24h to prepare Li2S8 positive electrode electrolyte;
[0118] A circular carbon paper with a diameter of 12 mm was used to prepare the current collector;
[0119] The Cu single atom material was dispersed in ethanol and then drop-coated on the current collector. The electrode was dried at 60°C overnight, and the coating loading was controlled to be about 0.5 mg / cm 2 To make a comparison electrode sheet;
[0120] During assembly, 40 μL of Li2S8 positive electrolyte was dripped onto the comparative electrode sheet, and after adding the separator, 20 μL of blank electrolyte was dripped. The blank electrolyte was prepared by replacing the lithium sulfide in the above Li2S8 positive electrolyte with lithium nitrate. The negative electrode used a metal lithium sheet to assemble a lithium-sulfur battery with Cu single-atom material.
[0121] In order to evaluate the catalytic performance of the CuCo double single-atom material of the present application and the Cu single-atom material in Comparative Example 1, a lithium sulfide nucleation experiment was performed based on the lithium-sulfur batteries prepared in the above-mentioned lithium sulfide nucleation experiment 1 and lithium sulfide nucleation experiment 2, and the catalytic performance of the two materials was evaluated by the lithium sulfide nucleation experiment.
[0122] The lithium sulfide nucleation experiment was conducted using a blue electric tester system produced by Shenzhen Kejing Zhida Technology Co., Ltd. The experimental conditions were: 25°C, voltage range 1.8-2.7V. During the experiment, the constant current 0.112mA was first discharged to 2.06V, and then switched to constant potential mode, keeping the voltage at 2.05V for lithium sulfide nucleation growth.
[0123] The results of the lithium sulfide nucleation experiment based on the lithium sulfide battery prepared in the lithium sulfide nucleation experiment 1 and the lithium sulfide nucleation experiment 2 are as follows Figure 2 As shown, Figure 2 The solid line in the figure is the lithium sulfide nucleation experimental data of the lithium sulfide battery containing CuCo double single-atom material prepared in the lithium sulfide nucleation experiment 1, and the dotted line is the lithium sulfide nucleation experimental data of the lithium sulfide battery containing Cu single-atom material prepared in the lithium sulfide nucleation experiment 2, wherein the coordinates of the intersection A are (4.10k, 0.059), the coordinates of the intersection B are (13.65k, 0.264), the coordinates of the intersection C are (9.80k, 0.432), and the coordinates of the intersection D are (12.16k, 0.286).
[0124] Depend on Figure 2 It can be seen that Figure 2The area of the region enclosed by the solid line and the horizontal and vertical axes is greater than the area of the region enclosed by the dotted line and the horizontal and vertical axes, especially the area between the intersection A and the intersection D. This also shows that compared with the lithium-sulfur battery prepared in the lithium sulfide nucleation experiment 2, the lithium-sulfur battery prepared in the lithium sulfide nucleation experiment 1 has better nucleation ability and can better induce lithium sulfide deposition. This also shows that the CuCo double single atom material prepared in Example 3 has a better catalytic effect and can better catalyze the redox process of polysulfides.
[0125] In the following example 4, a lithium-sulfur battery is prepared based on the CuCo double single-atom material prepared in examples 1 to 3, and in comparative example 2, a lithium-sulfur battery is prepared based on the Cu single-atom material prepared in comparative example 1.
[0126] It should be noted that the CuCo di-monoatom material prepared in the implementation methods of Examples 1 to 3 is used in Example 4, that is, the CuCo di-monoatom material obtained in any one of Examples 1 to 3 can be selected, or a mixed product of the CuCo di-monoatom materials prepared in any two examples can be selected, or a mixed product of the CuCo di-monoatom materials prepared in three examples can be selected. The following preparation of a lithium-sulfur battery is carried out using the CuCo di-monoatom material prepared in Example 3 as the material in Example 4 and the Cu single-atom material prepared in Comparative Example 1 as the material in Comparative Example 2.
[0127] Embodiment 4:
[0128] The sublimated sulfur solid powder was evenly mixed with the CuCo double single atom material prepared in the above Example 3 at a mass ratio of 8:2, and then heated at 155° C. for 12 h under a nitrogen atmosphere, and then cooled to room temperature to prepare a CuCo-S sulfur positive electrode.
[0129] The CuCo-S sulfur positive electrode and the binder PVDF were weighed in a mass ratio of 9:1, and a certain proportion of N-methylpyrrolidone was added to mix and adjust into a slurry. The slurry was evenly coated on the aluminum foil current collector with a coating machine, and then dried and cut to make a positive electrode sheet. The diameter of the positive electrode sheet was 14 mm, and the sulfur loading was 2 mg / cm 2 about.
[0130] LiTFSI was dissolved in a DOL / DME mixed solution with a volume ratio of 1:1 to prepare a 1.0 mol / L LiTFSI DOL / DME solution, and LiNO3 was added to the LiTFSI DOL / DME solution, wherein the mass fraction of LiNO3 was 2%, to prepare an electrolyte.
[0131] A lithium-sulfur battery is assembled using the CuCo-S sulfur positive electrode as a positive electrode sheet, a metal lithium sheet as a negative electrode sheet, celgard as a separator and an electrolyte, wherein the liquid-sulfur ratio (E / S) of the lithium-sulfur battery is 10 μL / mg.
[0132] Comparative Example 2:
[0133] The sublimated sulfur solid powder was evenly mixed with the Cu single atom material prepared in the above comparative example 1 at a mass ratio of 8:2, and then heated at 155° C. for 12 h under a nitrogen atmosphere, and then cooled to room temperature to obtain a Cu-S positive electrode.
[0134] The Cu-S positive electrode and the binder PVDF were weighed in a mass ratio of 9:1, and a certain proportion of N-methylpyrrolidone (NMP) was added to mix and adjust into a slurry. The slurry was evenly coated on the aluminum foil current collector with a coating machine. After drying, it was cut into pole pieces with a diameter of 14 mm and weighed. The sulfur loading was 2 mg / cm 2 About to prepare a Cu-S positive electrode sheet.
[0135] LiTFSI was dissolved in a DOL / DME mixed solution with a volume ratio of 1:1 to prepare a 1.0 mol / L LiTFSI DOL / DME solution, and LiNO3 was added to the LiTFSI DOL / DME solution, wherein the mass fraction of LiNO3 was 2%, to prepare an electrolyte.
[0136] The above-mentioned Cu-S positive electrode sheet is used as the positive electrode, the metal lithium sheet is used as the negative electrode sheet, celgard is used as the separator and the electrolyte is assembled to obtain a lithium-sulfur battery, and the liquid-sulfur ratio (E / S) of the lithium-sulfur battery is 10 μL / mg.
[0137] In order to verify the battery performance of the lithium-sulfur battery prepared based on the CuCo double single-atom material of the present invention and the lithium-sulfur battery prepared based on the Cu single-atom material of Comparative Example 1, the following electrochemical test is performed using the Blue Electric Tester system produced by Shenzhen Kejing Zhida Technology Co., Ltd. to test the discharge capacity of the lithium-sulfur battery as the number of cycles and current density change. The test conditions are: carried out at 25°C, voltage range 1.8-2.7V. Among them, the standard capacity of the lithium-sulfur battery is 1672mAh / g, and the specific results obtained by the test are as follows Figure 1 shown.
[0138] Charge and discharge cycle test: The test process is to discharge first and then charge, and the charge and discharge cut-off voltage is 1.8-2.7V. Different cycle numbers correspond to different current densities (1C=1675mAh). One cycle is to complete one discharge and one charge.
[0139] The test results of electrochemical test are as follows Figure 1 As shown, Figure 1 The solid dots in the graph are the electrochemical test curves of the lithium-sulfur battery prepared in Example 4. Figure 1 The hollow dots in the graph are the electrochemical test curves of the lithium-sulfur battery prepared in Comparative Example 2. During the test, the discharge capacity of the battery was tested at a current density of 0.2C within 0-10 cycles, the discharge capacity of the battery was tested at a current density of 0.5C within 10-20 cycles, the discharge capacity of the battery was tested at a current density of 1.0C within 20-30 cycles, the discharge capacity of the battery was tested at a current density of 2.0C within 30-40 cycles, the discharge capacity of the battery was tested at a current density of 3.0C within 40-50 cycles, the discharge capacity of the battery was tested at a current density of 4.0C within 50-60 cycles, the discharge capacity of the battery was tested at a current density of 5.0C within 60-70 cycles, and the discharge capacity of the battery was tested at a current density of 0.2C within 70-80 cycles.
[0140] Depend on Figure 1 It can be seen that under the same current density and number of cycles, the discharge specific capacity of the lithium-sulfur battery containing the CuCo double single-atom material prepared in the above-mentioned Example 4 is better than the discharge specific capacity of the lithium-sulfur battery containing the Cu single-atom material prepared in the above-mentioned Comparative Example 2, and when the current density of the lithium-sulfur battery changes significantly, the lithium-sulfur battery prepared by the CuCo double single-atom material also has a stable discharge specific capacity. This also means that compared with the lithium-sulfur battery adding the Cu single-atom material in Comparative Example 2, the present invention adds the CuCo double single-atom material prepared by the two-step method to the positive electrode material, so that the lithium-sulfur battery prepared based on the positive electrode material has a better discharge specific capacity, and further indicates that the addition of the CuCo double single-atom material can increase the conversion rate of polysulfides, promote the uniform deposition of lithium sulfide, and greatly alleviate the shuttle effect of polysulfides, thereby greatly improving the specific capacity, rate performance and cycle performance of the lithium-sulfur battery.
[0141] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises sulfur and a CuCo double single-atom material, the sulfur is loaded on the CuCo double single-atom material, and the preparation method of the CuCo double single-atom material comprises the following steps: Step 1: Preparation of Cu single atom material: The inorganic salt is mixed with the copper metal organic framework material, and a Cu single atom material is obtained after a first heating treatment; Step 2: Preparation of CuCo double single atom materials: The Cu single-atom material, a cobalt source and a solvent are mixed to obtain a second mixed solution, and the second mixed solution is dried and then subjected to a second heat treatment to obtain the CuCo double single-atom material.
2. The positive electrode material according to claim 1, characterized in that The copper metal organic framework material is formed by the coordination of Cu atoms and organic ligands, and the organic ligands include 1,4-phthalic acid, trimesic acid or 2,5-dihydroxyterephthalic acid.
3. The positive electrode material according to claim 1, characterized in that The preparation method of CuCo double single atom material satisfies at least one of the following conditions: (1) The first heat treatment is performed under an inert atmosphere; (2) The temperature of the first heat treatment is 700° C. to 800° C.; (3) The treatment time of the first heating treatment is 2h to 5h; (4) The second heat treatment is performed under an inert atmosphere; (5) The temperature of the second heat treatment is 700° C. to 900° C.; (6) The treatment time of the second heat treatment is 2 hours to 5 hours.
4. The positive electrode material according to claim 1, characterized in that The preparation method of CuCo double single atom material satisfies at least one of the following conditions: (1) The cobalt source is vitamin B12; (2) The solvent is ethanol; (3) The inorganic salt includes KCl and NaCl.
5. The positive electrode material according to claim 1, characterized in that The preparation method further comprises: In the step 1, after the first heat treatment, pickling is performed using an acidic solution to obtain the Cu single atom material; wherein the pH value of the acidic solution ranges from 1 to 7.
6. The positive electrode material according to claim 1, characterized in that The copper metal organic framework material is prepared by the following method: The organic ligand is mixed with a solution containing copper ions, and the copper metal organic framework material is obtained through reaction.
7. A method for preparing the positive electrode material according to claim 1, characterized in that: The steps include: Sulfur is mixed with the CuCo double monoatom material and subjected to a third heating treatment to obtain the positive electrode material.
8. The method according to claim 7, characterized in that The sulfur is elemental sulfur; and / or The mass percentage of the sulfur and the CuCo double monoatom material is 9:1 to 6:
4.
9. The method according to claim 8, characterized in that The third heat treatment is performed under an inert atmosphere, the temperature of the third heat treatment is 130° C. to 160° C., and the treatment time is 10 h to 13 h.
10. A method for preparing CuCo double single atom material for lithium-sulfur battery, characterized in that: The steps include: Step 1: Preparation of Cu single atom material: The inorganic salt is mixed with the copper metal organic framework material, and a Cu single atom material is obtained after a first heating treatment; Step 2: Preparation of CuCo double single atom materials: The Cu single-atom material, a cobalt source and a solvent are mixed to obtain a second mixed solution, and the second mixed solution is dried and then subjected to a second heat treatment to obtain the CuCo double single-atom material.